Distributed relay assignment and power allocation for full-duplex two-way relaying in wireless sensor networks. (October 2017) - Li, Song; Li, Shuo; Sun, Yanjing
In this article, the joint relay assignment and power allocation for full-duplex two-way relaying in wireless sensor networks is considered. We investigated the weighted sum rate maximization problem under relay assignment constraints and total power constraints on each cooperative link, which turns out to be a mixed integer nonlinear programming problem. To tackle the challenging problem, we propose a distributed relay assignment and power allocation scheme by separating the original problem into two subproblems: relay assignment and power allocation. The relay assignment subproblem is solved by a stable matching approach based on Gale–Shapley algorithm, while the power allocation of each cooperative link is solved by sequential convex approximation method. Simulation results indicate the advantages of our proposed scheme.